Analysis of gender relations in modern social and human sciences (Journal of Philosophy Culture and Political Science, 2020)
Modern Kazakhstan is a multi-confessional state that provides absolutely equal rights to its citizens.The gender approach presupposes not only an innovative rethinking of the position of women,but also the search for practical ways to free her from outdated ideas about herself and her role in themodern world. The article describes the processes of the development of gender relations in the socialand humanitarian sciences, and also gives their new models adopted in Kazakhstan, in particular inthe field of political science, law, economics and religious studies. Based on the results of the rankingon gender equality, developed by the international community, the results of political, economic, religiousand legal research in Kazakhstan are analyzed. Kazakhstani society is characterized by its ownconsistent development of modern gender relations in these areas.It should be noted that gender studies broadens the scope of innovation and research in sociology,including religion. First of all, this is due to the processes of secularization, modernization and emancipation.The question of the role and importance of gender studies and feminism in the field of religionarises in connection with the increase in the level of religiosity among women, which researchersinterpret in different ways, but most of these approaches are based on theoretical principles of gender.Key words: gender, politics, gender economy, religion.